2000
DOI: 10.1001/archpedi.154.4.355
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of Urgent Referrals by Nurses at a Hospital-Based Pediatric Call Center

Abstract: Objectives: To evaluate (1) the appropriateness of the after-hours referral (AHR), (2) clinical characteristics of urgently referred patients, and (3) parental compliance with disposition recommendations by the After-Hours Call Center of the Children's Hospital, Denver, Colo. Subjects:Patients of Denver, Colo, pediatricians who called after office hours were triaged by nurses using a computerized triage system, and were referred for afterhours evaluation to 1 of 5 urgent care sites (N = 409).Design: Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 35 publications
(21 reference statements)
3
42
1
Order By: Relevance
“…116 Most studies reported that a high proportion of referrals, often in excess of 90%, were appropriate. 131,140 Triage advice and referrals were more likely to be unnecessary than insufficient. 142 However, one study identified that acute and non-urgent scenarios were more likely to be classified correctly than urgent.…”
Section: Service Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…116 Most studies reported that a high proportion of referrals, often in excess of 90%, were appropriate. 131,140 Triage advice and referrals were more likely to be unnecessary than insufficient. 142 However, one study identified that acute and non-urgent scenarios were more likely to be classified correctly than urgent.…”
Section: Service Impactsmentioning
confidence: 99%
“…Of the 15 other studies, 72,89,100,101,[115][116][117][118][119]124,131,135,[138][139][140] four studies looked at the appropriateness of ED referrals. In terms of referral sources, no difference was found between telephone and self-referred patients, 118 but doctor-referred patients were the most appropriate referrals.…”
Section: Service Impactsmentioning
confidence: 99%
“…(8) This active preparation for the telenurses' questions appeared to calm the parents and decrease their worry.…”
Section: Preparation For Telenurse's Questionsmentioning
confidence: 99%
“…as to whether pediatric health calls are safe [8][9][10] or not [11] . Moreover, parents have reported both high [12,13] and low [14] satisfaction with the telephone service.…”
mentioning
confidence: 99%
“…6,7 The definition of a chronic condition was defined by a question from the Consumer Assessment of Health Plans Survey and included conditions that had lasted for at * Information presented is for entire call center; data in this study based on Denver Metro Area (number of MDs ϭ 153; number of providers ϭ 53; number of counties served ϭ 5; number of calls for winter ϭ 1509; number of calls for summer ϭ 1158; and number of calls for study period ϭ 1197). ** %2LT is the percentage that seems to be urgent per protocol and are referred, at the private physician's request, to the office's on-call physician for second level triage (2LT).…”
Section: Telephone Surveymentioning
confidence: 99%